2021
DOI: 10.1155/2021/6675790
|View full text |Cite
|
Sign up to set email alerts
|

A Client-Centric Evaluation System to Evaluate Guest’s Satisfaction on Airbnb Using Machine Learning and NLP

Abstract: Understanding the determinants of satisfaction in P2P hosting is crucial, especially with the emergence of platforms such as Airbnb, which has become the largest platform for short-term rental accommodation. Although many studies have been carried out in this direction, there are still gaps to be filled, particularly with regard to the apprehension of customers taking into account their category. In this study, we took a machine learning-based approach to examine 100,000 customer reviews left on the Airbnb pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 53 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…In addition, the number of parameters for a word embedding or a model that relies on word embeddings, such as recurrent neural networks, is usually a linear or quadratic function of dimensionality, which affects training time and computational costs [40]. Our study showed that this dimensionality is 100d for short texts, such as tweets or comments related to blog posts and 300d for long texts, such as IMDb comments or reviews left on Airbnb [41]. Indeed, mapping each word of the corpus on such a large number of dimensions, and even more so if the corpus is large, could increase the complexity of the model, slow down the training speed and add inferential latency, which has as a direct consequence, the impossibility to deploy the model on real tasks.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, the number of parameters for a word embedding or a model that relies on word embeddings, such as recurrent neural networks, is usually a linear or quadratic function of dimensionality, which affects training time and computational costs [40]. Our study showed that this dimensionality is 100d for short texts, such as tweets or comments related to blog posts and 300d for long texts, such as IMDb comments or reviews left on Airbnb [41]. Indeed, mapping each word of the corpus on such a large number of dimensions, and even more so if the corpus is large, could increase the complexity of the model, slow down the training speed and add inferential latency, which has as a direct consequence, the impossibility to deploy the model on real tasks.…”
Section: Discussionmentioning
confidence: 84%
“…Reference [37] used seven types of machine learning models to classify airline customer feedback sentiments into three classes and revealed that random forest had the best performance with an F1-score of 0.86. In addition to the studies reviewed above, machine learning has exhibited excellent efficiency in prediction tasks and is being actively applied in several domains [38][39][40][41].…”
Section: Machine Learning For Predictionmentioning
confidence: 99%
“…Regression is a method of modeling a variable (called target) as a function of independent predictors (called features), where the algorithm involved tries to find causal relationships between the variables [52].…”
Section: ) Linear Regressionmentioning
confidence: 99%